2020
DOI: 10.3390/ma13102253
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Printed Strain Hardening Cementitious Composites

Abstract: Extrusion based additive manufacturing of cementitious materials has demonstrated strong potential to become widely used in the construction industry. However, the use of this technique in practice is conditioned by a feasible solution to implement reinforcement in such automated process. One of the most successful ductile materials in civil engineering, strain hardening cementitious composites (SHCC) have a high potential to be employed for three-dimensional printing. The match between the tailored brittle ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…The other two directions D1 and D3 are perpendicular to the printing direction. The results obtained correspond with the observations of Figueiredo et al [26], who also observed reduced values of compressive strength in the direction of printing. The SHCC mixtures Ref and SE-CE delivered similar performance in the compression tests; see Figure 16a.…”
Section: Ultimate Compressive and Flexural Strengthsupporting
confidence: 91%
See 1 more Smart Citation
“…The other two directions D1 and D3 are perpendicular to the printing direction. The results obtained correspond with the observations of Figueiredo et al [26], who also observed reduced values of compressive strength in the direction of printing. The SHCC mixtures Ref and SE-CE delivered similar performance in the compression tests; see Figure 16a.…”
Section: Ultimate Compressive and Flexural Strengthsupporting
confidence: 91%
“…SHCC can be produced with low water-to-binder ratios, which enable the attainment of high compressive strength, reaching, if necessary, far beyond 100 MPa [23]. SHCC is also suitable for extrusion, which has been demonstrated in several studies [23][24][25][26]. Li et al [27] provided a comprehensive review of the progress in the development of printable SHCC.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies, however, indicate that the reality is more complex: particularly highly flexible fibers, such as the PVA and HDPE fibers used in ECCs, seem to orientate in the principal direction of flow. Initial results presented by Chaves Figueiredo et al [45] show fibers mainly orientate themselves diagonally in the u,v-plane, as a V-shape behind the nozzle, rather than parallel to the print path (Fig. 5).…”
Section: Extrudingmentioning
confidence: 89%
“…Another study that used 2 vol% 8 mm PVA fibers was presented by Chaves Figueiredo et al [19,45]. Two mixture concepts were developed into printable variants, one based on OPC and blast furnace slag binders and limestone aggregate, and another based on OPC and fly ash binders, and limestone and sand aggregates.…”
Section: Current Research In Printable Eccmentioning
confidence: 99%
“…Some of latest developments include reinforcement elements such as nails [20], staples [21] and screws [10]. A number of studies has also been done investigating the application of various fibres to improve material ductility [22][23][24][25][26][27][28]. Due to the process of 3DCP, most concepts suffer from high void content or not being validated on a large scale [38].…”
Section: State-of-the-artmentioning
confidence: 99%